α-Lipoic Acid Inhibits Helicobacter pylori-Induced Oncogene Expression and Hyperproliferation by Suppressing the Activation of NADPH Oxidase in Gastric Epithelial Cells - Byun, Eunyoung; Lim, Joo Weon; Kim, Jung Mogg; Kim, Hyeyoung (Mediators of Inflammation, 2014)
Hyperproliferation and oncogene expression are observed in the mucosa of Helicobacter pylori- (H. pylori-) infected patients with gastritis or adenocarcinoma. Expression of oncogenes such as β-catenin and c-myc is related to oxidative stress. α-Lipoic acid (α-LA), a naturally occurring thiol compound, acts as an antioxidant and has an anticancer effect. The aim of this study is to investigate the effect of α-LA on H. pylori-induced hyperproliferation and oncogene expression in gastric epithelial AGS cells by determining cell proliferation (viable cell numbers, thymidine incorporation), levels of reactive oxygen species (ROS), NADPH oxidase activation (enzyme activity, subcellular levels of NADPH oxidase subunits), activation of redox-sensitive transcription factors (NF-κB, AP-1), expression of oncogenes (β-catenin, c-myc), and nuclear localization of β-catenin. Furthermore, we examined whether NADPH oxidase mediates oncogene expression and hyperproliferation in H. pylori-infected AGS cells using treatment of diphenyleneiodonium (DPI), an inhibitor of NADPH oxidase. As a result, α-LA inhibited the activation of NADPH oxidase and, thus, reduced ROS production, resulting in inhibition on activation of NF-κB and AP-1, induction of oncogenes, nuclear translocation of β-catenin, and hyperproliferation in H. pylori-infected AGS cells. DPI inhibited H. pylori-induced activation of NF-κB and AP-1, oncogene expression and hyperproliferation by reducing ROS levels in AGS cells. In conclusion, we propose that inhibiting NADPH oxidase by α-LA could prevent oncogene expression and hyperproliferation occurring in H. pylori-infected gastric epithelial cells.